AEG-1 Regulates TWIK-1 Expression as an RNA-Binding Protein in Astrocytes - Hyun-Gug Jung; Ajung Kim; Seung-Chan Kim; Jae-Yong Park; Eun Mi Hwang (Brain Sciences, 2021)
AEG-1, also called MTDH, has oncogenic potential in numerous cancers and is considered a multifunctional modulator because of its involvement in developmental processes and inflammatory and degenerative brain diseases. However, the role of AEG-1 in astrocytes remains unknown. This study aimed to investigate proteins directly regulated by AEG-1 by analyzing their RNA expression patterns in astrocytes transfected with scramble shRNA and AEG-1 shRNA. AEG-1 knockdown down-regulated TWIK-1 mRNA. Real-time quantitative PCR (qPCR) and immunocytochemistry assays confirmed that AEG-1 modulates TWIK-1 mRNA and protein expression. Electrophysiological experiments further revealed that AEG-1 further regulates TWIK-1-mediated potassium currents in normal astrocytes. An RNA immunoprecipitation assay to determine how AEG-1 regulates the expression of TWIK-1 revealed that AEG-1 binds directly to TWIK-1 mRNA. Furthermore, TWIK-1 mRNA stability was significantly increased upon overexpression of AEG-1 in cultured astrocytes (p < 0.01). Our findings show that AEG-1 serves as an RNA-binding protein to regulate TWIK-1 expression in normal astrocytes.